REVIEW OF CRIMINAL LAW ON THE PROBLEM OF VIOLATION OF HEALTH PROTOCOL IN THE IMPLEMENTATION OF REGIONAL HEAD ELECTIONS (Perspective of the Pilkada Law System and the Quarantine Law in Indonesia) - Lubis, Mhd Teguh Syuhada (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
The spread of the virus that was never expected (or never anticipated) will reach Indonesia is still continuing. The Center for Mathematical Modeling and Simulation at the Bandung Institute of Technology estimates that this pandemic will reach its peak at the end of March and end in mid-April 2020. Even with the dynamics of existing data, these predictions may change. Based on the state of the Covid-19 outbreak, which continues to spread in the territory of Indonesia, the Government is making every effort to suppress its spread, including locking down in several places and also closing access to flights abroad. This effort is also carried out by the government to institutions that are said to be prone to being affected or places that can spread the Corona virus. The regulations for the implementation of the Regional Head General Election in Indonesia have undergone such changes, which are currently regulated in Law Number 6 of 2020 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2020 concerning the Second Amendment to Law Number 10 of 2016 concerning the Third Amendment to the Act. -Law Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors to become Laws. As well as several other laws and regulations related to the implementation of regional head elections. It becomes a problem when the Pilkada is constitutionally protected, but the crowds at the time of the Pilkada at each stage is an act that can be punished. This research is a normative legal research with descriptive analysis using secondary data sources. Based on the results of the research that the activities of implementing the Regional Head Elections are constitutionally protected by laws and regulations, especially Law Number 6 of 2020, but on the other hand, the Pilkada activities have the potential to cause crowds as evidenced by the implementation of the last 2020 Regional Head Elections which resulted in the spread of Covid-19 19 increased significantly. The crowd in question is included in actions that can be punished according to Law Number 6 of 2018. The problem of criminal law enforcement against health protocol violators in the post-conflict local election can at least be resolved by looking at each component in the legal system that directly affects law enforcement.